From Seeing to Understanding: The Conceptual Metaphor UNDERSTANDING IS LIGHT in Julian of Norwich's "Revelations of Divine Love" - Katarzyna Stadnik (Jesuit University Ignatianum in Krakow, 2024)
RESEARCH OBJECTIVE: The article discusses the interplay between language, cognition and culture from a cognitive diachronic perspective, focusing on the relation between religion and metaphorical thought. It investigates the role of the conceptual metaphor UNDERSTANDING IS LIGHT in religious discourse, using the example of The Revelations of Divine Love, written by Julian of Norwich, a late medieval anchoress. THE RESEARCH PROBLEM AND METODS: The paper draws on the Extended Conceptual Metaphor approach, Zoltán Kövecses's elaboration of the Conceptual Metaphor Theory (CMT). The universalist bias of CMT means that the theory tends to ignore the sociocultural context of historical data, prioritising the influence of universal human embodiment on metaphorical thought. Using Kövecses's approach, the paper shows how the gap in CMT methodology may be bridged to yield more reliable results. THE PROCESS OF ARGUMENTATION: The present study connects Kövecses's approach to Cognitive Linguistic research into sociocultural situatedness. To exemplify the problem, the analysis examines the cognitive‑cultural underpinnings of Julian's use of the metaphor UNDERSTAND‑ ING IS LIGHT. RESEARCH RESULTS: The analysis shows that the metaphorical conceptualisation pattern may well derive from Julian's sociocultural situatedness. The paper indicates that the anchoress's metaphorical thought should be seen as embedded in the late medieval sociocultural context, rather than being considered solely in terms of universal aspects of embodiment. CONCLUSIONS, RECOMMENDATIONS AND THE APPLICATIVE VALUE OF RESEARCH: The study concludes that the idea of sociocultural situatedness may be pivotal in the analyses of historical texts. It seems important to incorporate this idea into Kövecses's approach, which may inform the methodology of cognitive diachronic research into metaphorical conceptualisations. Furthermore, the results may be applied to teaching students how to approach historical texts, helping them gain a better understanding of the relation between metaphorical thought and culture.